Greater fear reactivity and psychophysiological hyperactivity among infants with later conduct problems and callous-unemotional traits - Mills-Koonce, W. Roger (J Child Psychol Psychiatry, 2014)
BACKGROUND: Approximately one-third of children who meet criteria for conduct problems (CP) are also characterized by elevated callous-unemotional (CU) traits. This subgroup is at elevated risk for more pervasive and extreme levels of later antisocial behavior and has been characterized by a fearlessness temperament and blunted stress psychophysiology at older ages. The objective of this study is to examine group differences in fear reactivity and stress psychophysiology in infancy among children classified as having CP with CU (CP+CU), CP without CU (CP-only), or no CP in later childhood. METHODS: A birth cohort study (n = 1,292) was followed longitudinally from birth through 1(st) grade. Behavioral fear, baseline heart period (HP) and respiratory sinus arrhythmia (RSA), and pre-task, 20-min post-task and 40-min post-task salivary cortisol were assessed at 6 and 15 months of age around a fear challenge task. CP and CU were assessed by maternal report at 1(st) grade and children were classified into CP and CU groups if they scored in the upper 10(th) percentile of these ratings. RESULTS: No group differences were observed in children at 6 months of age. However, at 15 months of age children with later CP+CU displayed greater high-intensity fear behavior, higher pre-task and overall cortisol levels, and lower levels of HP and RSA compared to children with CP-only and children with no CP. CONCLUSIONS: The discrepancy between the biobehavioral correlates of conduct problems with callous-unemotional traits in infancy and those reported from studies of older children and adults suggests that the etiology of this behavioral phenotype may be more complex than a simple genetic maturation model.